Integrating energy markets: Implications of increasing electricity trade on prices and emissions in the western United States - Dahlke, Steven (International Journal of Sustainable Energy Planning and Management, 2020)
This paper presents empirically-estimated average hourly relationships between regional electricity trade in the western United States (U.S.) and prices, emissions, and generation from 2015 through 2018. Consistent with economic theory, the analysis finds a negative relationship between electricity price in California and regional trade, conditional on local demand. Each 1 gigawatt-hour (GWh) increase in California electricity imports is associated with an average $0.15 per megawatt-hour (MWh) decrease in the California Independent System Operator’s (CAISO) wholesale electricity price. There is a net-negative short-term relationship between carbon dioxide emissions in California and electricity imports that is partially offset by positive emissions from exporting neighbors. Specifically, each 1 GWh increase in regional trade is associated with a net 70-ton average decrease in CO2 emissions across the western U.S., conditional on demand levels. The results provide evidence that electricity imports mostly displace natural gas generation on the margin in the California electricity market. A small positive relationship is observed between short-run SO2 and NOx emissions in neighboring regions and California electricity imports. The magnitude of the SO2 and NOx results suggest an average increase of 0.1 MWh from neighboring coal plants is associated with a 1 MWh increase in imports to California.